Karol Wojtyła's Katolicka Etyka Społeczna as Precursor and Hermeneutic Key to Pope John Paul II's Economic Teaching. (8th October 2020) - Beyer, Gerald J.
Abstract: The highly anticipated publication of Karol Wojtyła's Katolicka etyka społeczna (KES) in 2018 provides a novel and important basis for understanding the economic thinking of Pope John Paul II. The text is comprised of Wojtyła's extensive lecture notes from the 1950s on the topic of Catholic social teaching and spans almost 500 pages. KES illustrates the future pope's deep concern for economic justice as a young priest and his ambivalence towards capitalism, which persisted throughout his papacy. Given the size of KES, this article selectively focuses on Wojtyła's treatment of topics of continuing relevance: the right of the Church to pronounce on economic matters; private property and the "social mortgage" on it; inequality, the just distribution of resources, and the "option for the poor"; the moral assessment of capitalism and Marxism; the dignity of labor and workers' rights; and the role of conflict in promoting the common good. I contend that KES is consonant with the later papal teaching of John Paul II on economic justice and that it provides a hermeneutic key to understanding it. Furthermore, I argue that the "radicalism" of Karol Wojtyła on matters of economic justice in KES coheres with papal social teaching from Pope Paul VI through that of Pope Francis.